A new method for ultrasonic fatigue testing of equibiaxial and pure shear cruciform specimens. (November 2021) - da Costa, Pedro R.; Reis, Luís; Montalvão, Diogo; Freitas, Manuel
Highlights: A new method - F requency D omain D ecomposition - was adapted to ultrasonic fatigue. The FDD method proved supportive for ultrasonic methods development and validity. 3 cruciform geometries were successfully tested in the ultrasonic fatigue method. Fatigue failure was achieved in both in-phase and out-of-phase cruciform specimens. Crack initiation and propagations showed similar behaviour to conventional methods. Abstract: Mechanical and material testing and analysis are of indisputable importance. As the variety of materials and/or the complexity of products grows, so does the need for new material characterisation methods. In this study, experimental results from a new method for ultrasonic fatigue testing of equibiaxial and pure shear cruciform specimens is presented and validated. The method uses specially designed cruciform specimens' geometries for ultrasonic fatigue testing machines. Three different cruciform geometries were tested. The responses from the specimens were first studied by an adapted modal calculation method FDD. The new method allows determining fatigue strength of cruciform specimens in the VHCF regime with very satisfactory results.